About some restrictions on holistic recognition of ethics of legal professions - Górna, Izabela (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The paper raises significant problems concerning a role and importance of legal professions in the modern world. The paper analyses the ethical challenges postulated to the judge and posed to attorneys and legal advisers. Some consideration is given to different ways of the understanding of professional ethics, in particular from the point of view of ethics organizing corporations and the ethics seen as caring about the quality of law in a moral dimension. An opinion is expressed that it is impossible to determine the ethical principles guiding practice of the legal profession in a one-dimensional way, especially that of a judge, an attorney or a legal adviser.